2019
DOI: 10.1016/j.tree.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Towards Integrating Evolution, Metabolism, and Climate Change Studies of Marine Ecosystems

Abstract: Global environmental changes are challenging the structure and functioning of ecosystems. However, a mechanistic understanding of how global environmental changes will affect ecosystems is still lacking. The complex and interacting biological and physical processes spanning vast temporal and spatial scales that constitute an ecosystem make this a formidable problem. A unifying framework based on ecological theory, that considers fundamental and realized niches, combined with metabolic, evolutionary, and climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 86 publications
0
15
0
1
Order By: Relevance
“…Importantly, this approach can also help inform future experimental designs aimed at testing the probability of adaptive outcomes across multivariate environments through the analysis of a select set of traits. We are at a critical juncture where we need ecosystem and biogeochemical models to incorporate evolutionary dynamics in order to robustly predict future shifts in ecosystem dynamics [ 33 ]. Due to the seemingly infinite amount of possible interacting biological and environmental variables to test, evolutionary and mathematical tools that allow us to efficiently combine experiments with modelling will be critical to help predict microbial population responses to future global change scenarios through the lens of evolutionary phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this approach can also help inform future experimental designs aimed at testing the probability of adaptive outcomes across multivariate environments through the analysis of a select set of traits. We are at a critical juncture where we need ecosystem and biogeochemical models to incorporate evolutionary dynamics in order to robustly predict future shifts in ecosystem dynamics [ 33 ]. Due to the seemingly infinite amount of possible interacting biological and environmental variables to test, evolutionary and mathematical tools that allow us to efficiently combine experiments with modelling will be critical to help predict microbial population responses to future global change scenarios through the lens of evolutionary phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…We are at a critical juncture where we need ecosystem and biogeochemical models to incorporate evolutionary dynamics in order to robustly predict future shifts in ecosystem dynamics [33]. Due to the seemingly infinite amount of possible interacting biological and environmental variables to test, evolutionary and mathematical tools that allow us to efficiently combine experiments with modeling will be critical to help predict microbial population responses to future global change scenarios through the lens of evolutionary phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, a growing body of literature has shown that genetic architecture influences how traits and trait correlations are impacted by environmental shifts and that these shifts produce nonrandom distributions of phenotypes [29][30][31]. These studies have substantial consequences for understanding future shifts in marine phytoplankton function and thus carbon cycling and global climate [32,33]. However, there have been few attempts to investigate the implications of this phenomenon for the evolution of trait and trait correlations of photosynthetic microbes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Often, organism reactions to a changing condition include the remodeling of their metabolism and regulating the levels of specific metabolites, which can potentially represent markers of a particular response (e.g., biotic or abiotic stresses). In this context, metabolomics helps the evaluation of the impact of climate changes on marine organisms, unraveling contributions that marine systems could play in mitigating the effects of global warming [259,260].…”
Section: Bioinformatics Applications and Resources In Marine Omicsmentioning
confidence: 99%